2018
DOI: 10.1111/efp.12437
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and tolerance of Douglas‐fir seedlings to artificial inoculation with the fungus Ophiostoma pseudotsugae

Abstract: Summary We tested the resistance and tolerance of 79 Douglas‐fir halfsibling seedling families to artificial inoculation with Ophiostoma pseudotsugae in a shade house experiment. The Douglas‐fir beetle vectors the fungus where it colonizes the phloem and sapwood, often leading to tree mortality. The 79 halfsibling seedling families originated from four seed planning zones in BC that span ecological gradients ranging from moist‐warm to cool‐wet. We tested resistance to the fungus by measuring lesion size and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Lessons from other vascular pathosystems showed that the compartmentalization of the pathogen represents a first line of defence, its efficacy having a significant contribution to the overall disease outcome (Beckman & Roberts, 1995;Fradin & Thomma, 2006). Mechanisms of tolerance can therefore operate independently of those of resistance to mitigate the effects of infection on host physiology, and promote its performance and longevity (Cruickshank et al, 2018;Fradin & Thomma, 2006;Rusli, Idris, & Cooper, 2015). In contrast to genotypes from the F2 progeny, all pure V. vinifera genotypes tested in this study presented a poor healing ability upon P. chlamydospora infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lessons from other vascular pathosystems showed that the compartmentalization of the pathogen represents a first line of defence, its efficacy having a significant contribution to the overall disease outcome (Beckman & Roberts, 1995;Fradin & Thomma, 2006). Mechanisms of tolerance can therefore operate independently of those of resistance to mitigate the effects of infection on host physiology, and promote its performance and longevity (Cruickshank et al, 2018;Fradin & Thomma, 2006;Rusli, Idris, & Cooper, 2015). In contrast to genotypes from the F2 progeny, all pure V. vinifera genotypes tested in this study presented a poor healing ability upon P. chlamydospora infection.…”
Section: Discussionmentioning
confidence: 99%
“…This finding raises questions about the potential weight of these different traits (i.e., resistance vs. tolerance) on the overall host susceptibility as seen in the field. The NLL has been widely used as a marker of genotype susceptibility to vascular pathogen (Cruickshank, Bleiker, Sturrock, Becker, & Leal, 2018; Eskalen et al, 2001; Travadon et al, 2013). On the other hand, bioassays performed on detached leaves, callus and in vitro plantlets, also stressed that physiological processes, such as the induction of defence, were differentially affected across genotypes while they are exposed to the wood pathogens or to the toxins they secreted (Cardot et al, 2019; Lambert et al, 2013; Stempien et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Low host genetic control over this disease was not expected. Two related trials of the same interior Douglas‐fir families showed moderate resistance to Armillaria ostoyae (Cruickshank et al., 2010) and resistance and tolerance to Ophiostoma pseudotsugae (Cruickshank et al., 2018). Both of these studies detected differences in resistance at the zone and family level, with the warmer zones SA and WKL both having increased resistance to the pathogens.…”
Section: Discussionmentioning
confidence: 99%